2020
DOI: 10.1002/da.23112
|View full text |Cite
|
Sign up to set email alerts
|

Network analysis of PTSD and depressive symptoms in 158,139 treatment‐seeking veterans with PTSD

Abstract: Background: In recent years, a new framework for analyzing and understanding posttraumatic stress disorder (PTSD) was introduced; the network approach. Up until now, network analysis studies of PTSD were largely conducted on small to medium sample sizes (N < 1,000), which might be a possible cause of variability in main findings.Moreover, only a limited number of network studies investigated comorbidity.Methods: In this study, we utilized a large sample to conduct a network analysis of 17 symptoms of PTSD (DSM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
26
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(42 citation statements)
references
References 42 publications
5
26
1
Order By: Relevance
“…The strongest associations were identified between the symptoms "hypervigilant" and "easily startled", "internal avoidance" and "external avoidance", "emotional numbing" and "feeling detached", as well as "feeling detached" and "loss of interest". These results aligned well with results from a previously reported review on PTSD symptom network (Birkeland et al, 2020), with a recent analysis of a large sample of veterans (Duek et al, 2020), as well as with the example described in Section 7.1, which analyzes a subset of the larger dataset discussed in Isvoranu et al (2020).…”
Section: Empirical Applicationsupporting
confidence: 89%
“…The strongest associations were identified between the symptoms "hypervigilant" and "easily startled", "internal avoidance" and "external avoidance", "emotional numbing" and "feeling detached", as well as "feeling detached" and "loss of interest". These results aligned well with results from a previously reported review on PTSD symptom network (Birkeland et al, 2020), with a recent analysis of a large sample of veterans (Duek et al, 2020), as well as with the example described in Section 7.1, which analyzes a subset of the larger dataset discussed in Isvoranu et al (2020).…”
Section: Empirical Applicationsupporting
confidence: 89%
“…However, our findings suggest that caution is needed when interpreting specific associations in networks and when interpreting differences in the magnitude of associations within a single cross-sectional network. It is worth noting that we identified few differences in comparing the networks, suggesting that associations remained relatively stable even across cross-sectional samples (as has been found by other researchers, for instance in the context of post-traumatic stress disorder, Duek et al, 2021 ).…”
Section: Discussionsupporting
confidence: 78%
“…4. (Duek et al 2021), as well as with the example described in Sect. 7.1, which analyzes a subset of the larger dataset discussed in (Isvoranu et al in press) In terms of centrality-descriptive statistics often used in network analysis in attempts to identify the most influential nodes (Bringmann et al 2019)-the extended meta-analysis identified especially the symptoms "feeling detached".…”
Section: Empirical Application: a Meta-analysis Of 52 Ptsd Datasetsmentioning
confidence: 93%